2008
DOI: 10.1021/la800963u
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Surface Area of Pd and Nanometric Au Aggregates Supported on a Micrometric Solid Support by Thiol Adsorption and GC−MS

Abstract: A new sensitive and specific method to measure gold and palladium surface areas using alkanethiol adsorption coupled with analysis by gas chromatography with mass spectrometry detection has been developed. The effectiveness of the method was tested with metallic samples having a known surface area. The results have also been compared with BET specific surface area measurements. The results obtained with both methods show a good correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Various studies reported on the supported M-NP surface area determination using organothiol as probe molecules. It was shown that the surface areas of supported M-NPs as determined by organothiol adsorption method are in agreement with those calculated on the basis of the theoretical models and characterization [150,233,253,255,261,262]. Table 1 shows some examples.…”
Section: Determination Of the Surface Area And Particle Sizes Of Metal Nanoparticlessupporting
confidence: 66%
See 2 more Smart Citations
“…Various studies reported on the supported M-NP surface area determination using organothiol as probe molecules. It was shown that the surface areas of supported M-NPs as determined by organothiol adsorption method are in agreement with those calculated on the basis of the theoretical models and characterization [150,233,253,255,261,262]. Table 1 shows some examples.…”
Section: Determination Of the Surface Area And Particle Sizes Of Metal Nanoparticlessupporting
confidence: 66%
“…Nevertheless, those methods require expensive instrumentations and are limited by the properties of the support. Thus, chemisorption methods, using organothiols as probe molecules, are theoretically appropriate for the determination of the specific surface area of supported M-NPs [150,233,253,261,262]. The method, therefore, does not require dedicated and expensive equipment, and tedious sample preparation.…”
Section: Determination Of the Surface Area And Particle Sizes Of Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, true surface area and particle size determination are key aspects of the activity of metal nanoparticle catalysts. Chemisorption methods using organothiols as probe ligands are in principle suitable for the specific surface area determination of the supported AuNPs [39][40][41][42]. It was reported that no adsorption is observed, except for CuO and AgO, when organothiols are exposed to oxidic supports [43].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven through investigations that anchoring metal nanoparticles on supports is an effective approach to solve the above two drawbacks. [5][6][7] Therefore, many materials with active sites for anchoring metal nanoparticles have been developed as candidates for catalyst supports. Of the wide range of supports, hollow capsules have attracted considerable interest due to their low density, high surface area and large void volume.…”
Section: Introductionmentioning
confidence: 99%